Cover Feature: Institute Feature: IOCB Prague (Eur. J. Org. Chem. 37/2018). Issue 37 (12th September 2018) - Hocek, Michal; Hostomský, Zdeněk
Abstract : The Cover Feature shows the front entrance of the Institute of Organic Chemistry and Biochemistry of the Czech Academy of Sciences (IOCB) in Prague. It highlights Tenofovir, a clinical antiviral agent used for the treatment of HIV and Hepatitis B, which was discovered at the IOCB. More information on the institute and the research performed there can be found in theGuest Editorial by Z. Hostomský of the special issue "Institute Feature: IOCB."